ANALYSIS OF THE MANAGEMENT INDICATORS OF THE MOBILE EMERGENCY CARE SERVICE OF CEARÁ - Natália Pinheiro Fabricio Formiga; Lucilane Maria Sales da Silva; José Hiago Feitosa de Matos; Emiliana Bezerra Gomes; Kelly Fernanda Silva Santana; Francisco Edilson Ferreira; Maria Veraci Oliveira Queiroz (Cogitare Enfermagem)
Objective: To analyze the health management indicators related to the mobile emergency care service in Ceará.